Pulmonary Sequestration with Renal Aplasia and Elevated SUV Level in PET/CT - Serdar Şen; Nilgün Kanlıoğlu Kuman; Ekrem Şentürk; Engin Pabuşcu; Ertan Yaman (Case Reports in Pulmonology)
Extralobar sequestration with other bronchopulmonary malformations is commonly seen; however, the association of extralobar sequestration with renal aplasia is very rare. A 75-year-old female patient was admitted with back pain. Ultrasonography revealed aplasia of the left kidney and tomography showed 6×4.5 cm sized tumor in the left hemithorax at the posterobasal area. The lesion has focally increased glycolytic activity (SUVmax: 3.2) at the left upper pole on positron emission tomography scan (PET/CT). Sequestrectomy was performed after the confirmation by frozen section that the lesion was benign and of extrapulmonary sequestration. No complication occurred during postoperative and 50-month follow-up period.